Teaching foreign languages to the students based on interaction hypothesis: Teaching foreign languages to the students based on interaction hypothesis - Majidova, Gulruh (Maktabgacha taʼlim jurnali, 2022)
Abstract: The Interaction hypothesis is a theory that deals with acquiring second language within which language proficiency and its development is improved by interacting and communicating face-to face. The significance of input that teaching materials given to the learners, interaction and communication using second language and output the learners produce is on the second focus in second language acquisition. According to this hypothesis the degree of language complexity namely input should be proportional to the learner’s proficiency level meaning that the learners should be able to comprehend the input they are exposed to. In second language acquisition (SLA) interaction is undistinguishable component within which the learners have to use the target language while negotiating with each other.